2009
DOI: 10.1111/j.1751-1097.2008.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Photocycles of Channelrhodopsin‐2

Abstract: Recent developments have used light-activated channels or transporters to modulate neuronal activity. One such genetically-encoded modulator of activity, channelrhodopsin-2 (ChR2), depolarizes neurons in response to blue light. In this work, we first conducted electrophysiological studies of the photokinetics of hippocampal cells expressing ChR2, for various light stimulations. These and other experimental results were then used for systematic investigation of the previously proposed three-state and four-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
301
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(330 citation statements)
references
References 25 publications
20
301
0
1
Order By: Relevance
“…To determine if changes in spiking occurred with a time course similar to that of the light pulses we delivered, we next stimulated with square pulses and measured spiking in small neuronal populations. Consistent with ChR2 kinetic properties (activation time constant = 1.5 ms, deactivation time constant ∼5 ms) (29), the duration of firing rate changes matched the duration of pulses. Higher-amplitude light pulses also produced larger changes in average firing rate ( Fig.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…To determine if changes in spiking occurred with a time course similar to that of the light pulses we delivered, we next stimulated with square pulses and measured spiking in small neuronal populations. Consistent with ChR2 kinetic properties (activation time constant = 1.5 ms, deactivation time constant ∼5 ms) (29), the duration of firing rate changes matched the duration of pulses. Higher-amplitude light pulses also produced larger changes in average firing rate ( Fig.…”
Section: Resultssupporting
confidence: 62%
“…4 C and D, we dropped any measurements with a mean rate below 0.02 spikes/s, because 90-110 measurements did not produce reliable estimates for these low rates; this rate was below the behavioral detection threshold of 0.11 spikes/s. To determine if ChR2 conductance varied linearly with light duration and amplitude, we implemented the four-state ChR2 biophysical model of Nikolic et al (29,31). Simulations confirmed that, at low light levels, neither desensitization nor saturation causes nonlinearities (Fig.…”
Section: Data Inmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, in CrChR2 two conducting states have been recognized by their different relative permeability to H + and Na + (23,24). A model of two interconnected photocycles, each of which contains a closed (nonconducting) state and an open (conducting) state, has been developed for CCRs (25)(26)(27). However, single-turnover photocurrents generated by CrChR2 upon laser excitation decay monoexponentially (28,29), which means that the second conducting state accumulates only under continuous light, indicating that the second state requires secondary photochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the strength of the connections is scaled by the number of neurons that send the afferents. The ChR2 depolarization is modeled by only two states (open and closed) because we are analyzing the slow dynamics of the system (30). Therefore, ChR2 is modeled using I ChR2 ¼ g ChR2 hðtÞðV S − 0 mVÞ, where the reverse potential is set to 0 mV as suggested by Talathi …”
Section: Methodsmentioning
confidence: 99%